Development of central retinal artery occlusion accompanied by choroidal folds in a patient with antineutrophil cytoplasmic antibody-associated vasculitis: A case report. Issue 35 (28th August 2020) - Takagi, Mai; Kobayashi, Takatoshi; Kida, Teruyo; Takai, Nanae; Shoda, Hiromi; Maruyama, Koichi; Tada, Rei; Makino, Shigeki; Ikeda, Tsunehiko
Abstract: Rationale: We report a case of central retinal artery occlusion (CRAO) accompanied by choroidal folds in a patient positive for myeloperoxidase (MPO)-antineutrophil cytoplasmic antibody (ANCA). Patient concerns: The study involved a 67-year-old female patient who presented at the Department of Ophthalmology, Osaka Medical College, Takatsuki-City, Osaka, Japan on October 24, 2016 after becoming aware of a sudden decrease of visual acuity (VA) in her right eye. Other than suffering with scleritis 6-months previous, there was no obvious past history. Diagnosis: Upon examination, the VA in her right eye was hand motion, and the anterior segment of that eye showed thinning of the superior sclera. Macular edema in the inner retina and cherry red spots were observed in the ocular fundus, and optical coherence tomography (OCT) findings showed hyperreflectivity of the inner retina and choroidal folds. Fluorescein angiography (FA) examination of the fundus showed scattered areas of no retinal perfusion, and indocyanine green angiography (IA) findings of the fundus indicated a possible choroidal circulatory disturbance in her right eye. Blood test findings revealed the patient to be positive for MPO-ANCA. Based on the above findings, the patient was diagnosed with CRAO and choroidal circulatory disturbance due to ANCA-associated vasculitis. Interventions: For treatment, steroid semi-pulse therapy was initiated. Outcomes: Post treatment initiation, the fundus features and choroidal folds gradually improved, and her VA slightly improved to 0.08. Lessons: Based on the FA, IA, and OCT findings, the present case was considered to have CRAO accompanied by choroidal circulatory disturbance due to ANCA-associated vasculitis, a rare disease that may be complicated by choroidal circulatory disturbances.